Haiti Systematic Country Diagnostic Update : Pathways to Responding to Recurrent Crises and Chronic Fragility - World Bank (Washington, DC, 2022)
Haiti's economic and social development continues to be hindered by political instability, corruption, and fragility. This Systematic Country Diagnostic (SCD) Update draws on existing and new analysis, publications, and extensive consultations and ongoing dialogue with public and private sector stakeholders in Haiti. Throughout the discussions, there was broad consensus on the diagnosis of challenges, in particular the country’s weak governance, as well as the priorities ahead. The document is structured as follows: Chapter 1 examines trends in poverty and shared prosperity in Haiti; Chapter 2 analyzes growth trends and challenges; Chapter 3 identifies risks to the sustainability of development; and the final chapter takes stock of these elements and identifies priorities ahead, building on those identified in the 2015 SCD.